2004
DOI: 10.5194/aab-47-287-2004
|View full text |Cite
|
Sign up to set email alerts
|

Slaughter value and meat quality of Muscovy ducks, Pekin ducks and their crossbreeds, and evaluation of the heterosis effect

Abstract: Slaughter value and meat quality of Muscovy ducks, Pekin ducks and their crossbreeds, and evaluation of the heterosis effect AbstractThe studies were conducted on 200 Muscovy ducks, 100 Pekin ducks of the A-44 strain and 200 their crossbreeds (sex ratio: 1:1). The ducks were fed complete commercial diets, appropriate for respective species. Slaughter and slaughter value estimation were performed at the age of: 7 weeks -for males and females of the A-44 strain, 10 weeks -for Muscovy females, and 12 weeks -for M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
5
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 6 publications
9
28
5
2
Order By: Relevance
“…From the point of view of breeding maintaining genetically diversified conservative flocks of birds is necessary to give rise to genetic variation in the selected populations (KSIĄŻKIEWICZ, 2003). These conservative flocks were used in the development of new breeding and experimental strains and synthetic lines as well as in the search for heterosis effects in commercial sets (KISIEL and KSIĄŻKIEWICZ, 2004;WAWRO et al, 2004;WOŁOSZYN et al, 2006). The world's genetic resources conservation programme currently includes 11 Polish goose populations maintained in Poland, including Suwałki geese -Su, Kartuzy geese -Ka, Kielce geese -Ki and Subcarpathian geeseSb (http://bioroznorodnosc.izoo.krakow.pl/gesi).…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of breeding maintaining genetically diversified conservative flocks of birds is necessary to give rise to genetic variation in the selected populations (KSIĄŻKIEWICZ, 2003). These conservative flocks were used in the development of new breeding and experimental strains and synthetic lines as well as in the search for heterosis effects in commercial sets (KISIEL and KSIĄŻKIEWICZ, 2004;WAWRO et al, 2004;WOŁOSZYN et al, 2006). The world's genetic resources conservation programme currently includes 11 Polish goose populations maintained in Poland, including Suwałki geese -Su, Kartuzy geese -Ka, Kielce geese -Ki and Subcarpathian geeseSb (http://bioroznorodnosc.izoo.krakow.pl/gesi).…”
Section: Introductionmentioning
confidence: 99%
“…This live weight was within the optimum range recommended for beginning of force-feeding and guarantees a high-quality produce. Wawro et al (9) reported final male mullards body weight of 3.150 kg at 12 weeks of age. Salichon et al (10) and Beaza (11) …”
Section: Discussionmentioning
confidence: 99%
“…Penampilan yang berhubungan dengan produksi pada umumnya heterosis positif, sedang penampilan reproduksi pada umumnya heterosis efek negatif (Cassady et al, 2002). Dalam usaha untuk memperbaiki aktivitas diastatik gen yang memunculkan efek heterosis yang dikehendaki, perlu dilakukan seleksi secara ketat dan berulang pada kedua tetuanya terhadap sifat yang akan digabungkan, untuk memperoleh kedua tetua yang betul-betul baik dalam memunculkan heterosis yang baik pula (Cassady et al, 2002;Wawro et al, 2004;Baeza, 2006).…”
Section: Pendahuluanunclassified
“…Besarnya efek heterosis kualitas daging sangat ditentukan oleh kombinasi antara genetik kedua tetuanya yang didukung oleh usia dan nutrisi pakan yang diberikan (Baeza, 2006). Efek heterosis yang berasal dari efek genetik non aditif (dominan, over dominan, epistasis) yang selalu lebih nampak (Wawro et al, 2004). Empat jenis itik yang mempunyai urutan berat badan pada umur 10 minggu, dari terberat yaitu itik cherry-valley, entok, jinding dan sumuma oleh Wen-lin et al (2009) disilangkan antara entok dengan itik cherry-valley, jinding dan sumuma.…”
Section: Penampilan Itik Entok Dan Tiktok Betinaunclassified